How Social Media Marketing, Key Opinion Leaders, and e-WOM Shape Consumers' Purchase Decisions for Azarine Products - Khairunisa, Nur Fitra; Nora Andira Brabo; Agus Sriyanto (Jurnal Manajemen Dayasaing, 2025)
Globally, skincare and cosmetic products are not only a necessity but also a part of lifestyle. Consumers are becoming more selective in choosing products that suit their needs and preferences. Azarine Cosmetic is one of the local beauty brands that has successfully captured consumer attention by offering products tailored to Indonesian skin conditions and tropical climate. Social media marketing, KOLs, also e-WOM play a crucial role in shaping consumer purchasing behavior, particularly within the beauty sector. This study seeks to analyze how social media marketing, KOLs, also e-WOM on the purchasing decisions regarding to Azarine products. Employing a quantitative methodology, the study gathers survey data from participants aged 17 and older who are active on social media, follow Azarine products, and are familiar with the KOLs endorsing them. All 182 respondents meet the criteria to be included in the research sample. The dataset undergoes statistical processing through multiple regression analysis, facilitated by SPSS version 29 to ensure accurate interpretation of results. The findings indicate that social media marketing, KOLs, and e-WOM significantly influence consumer purchasing decisions, both independently and in conjunction. Additionally, the analysis demonstrates that these factors account for 82.8% of the variation in consumer purchasing decisions.